2013
DOI: 10.1177/1357633x13517352
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of remote patient monitoring for chronic heart failure patients

Abstract: We carried out a meta analysis of remote patient monitoring (RPM) for chronic heart failure (CHF) patients. A literature search was used to identify randomised controlled trials with more than 40 patients, published between February 2003 and February 2013. The primary outcome (mortality) was analysed using a random effect model. Thirteen studies were included (3337 patients). RPM resulted in a significantly lower mortality (risk ratio 0.76; 95% confidence interval 0.62 to 0.93) compared to usual care. The test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 25 publications
0
88
0
1
Order By: Relevance
“…These findings are consistent with multiple studies that also reported successful incorporation of HT with HF study participants in order to promote self-care resulting in both reductions and/or absences of hospital readmissions. [27][28][29][30][31][32] Patients in the HT Group A reported higher levels of being able to manage their HF self-care over time in contrast to participants in Groups B and C. This behavior specifically refers to the decision-making process in which patients recognize and respond to their symptoms. Self-care management is an active, deliberative process that is essential in HF self-care if patients are going to control the balance between relative health and symptomatic HF.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with multiple studies that also reported successful incorporation of HT with HF study participants in order to promote self-care resulting in both reductions and/or absences of hospital readmissions. [27][28][29][30][31][32] Patients in the HT Group A reported higher levels of being able to manage their HF self-care over time in contrast to participants in Groups B and C. This behavior specifically refers to the decision-making process in which patients recognize and respond to their symptoms. Self-care management is an active, deliberative process that is essential in HF self-care if patients are going to control the balance between relative health and symptomatic HF.…”
Section: Discussionmentioning
confidence: 99%
“…Research into intelligent healthcare solutions for this problem is however limited by the technology itself. Although sensors used in RPM have proven to be successful (Nakamura et al, 2013), activity and lifestyle monitoring has become an issue while using occupancy technologies such as PIR sensors, door sensors and chair sensors. There is also a large gap in the ability to provide monitoring for elderly who suffer from dehydration and malnourishment, a significant attributor to NCDs and death in that age group .…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al has demonstrated the efficacy of this method of remote, technology assisted care by examining the effectiveness of RPM in reducing the risk of mortality for CHF patients compared to 'usual care' (Nakamura et al, 2013. A significant factor in reducing mortality when using RPM has been the higher frequency of measurements from the patient as this allows for a greater amount of data to be examined and thus an intervention made timelier.…”
Section: Remote Patient Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…• Congestive heart failure -Automatic patient data transmission by means of monitoring devices is being used together with standard telephone calls to allow the assessment of symptoms and vital signs, as well as the transmission of automatic alarms (Conway, Inglis and Clark, 2014;Nakamura, Koga and Iseki, 2014) targeting older adults with congestive heart failure. Home monitoring is used mainly to minimize heart failure-related hospitalizations and all-cause mortality (Conway et al, 2014) when compared with usual care, but several secondary outcomes are also considered, such as self-care behaviour (e.g.…”
Section: Related Workmentioning
confidence: 99%